OPEN LABEL STUDY COMPARING THE EFFICACY OF CONTINUOUS LOW DOSE ISOTRETINOIN VERSUS INTERMITTENT LOW DOSE ISOTRETINOIN REGIMENS IN MODERATE TO SEVERE ACNE VULGARIS - Rehman, Farhat; Pirzada, Durreshehwar Arshad; Abdullah, Sumaira; Khan, Mahvish Aftab (Journal of Ayub Medical College Abbottabad, 2025)
Background: Acne vulgaris, recognized as the eighth most prevalent disease globally, affects approximately 9.4% of the world population. It can manifest in a spectrum ranging from mild physiologic acne to severe presentations such as nodules, cysts, and abscesses. This open-label comparative study was conducted at the Dermatology OPD of Akbar Niazi Teaching Hospital, Islamabad, from September 1, 2021, to March 1, 2022, with the objective of evaluating the efficacy of low-dose continuous versus low-dose intermittent oral isotretinoin in patients with moderate-to-severe acne vulgaris. Acne was defined by the presence of lesions—including papules, pustules, comedones, or cysts—with a Global Acne Grading System (GAGS) score of 19–30 indicating moderate and 31–38 indicating severe cases. Efficacy was defined as a greater than 80% reduction in the GAGS score after three months of treatment, calculated as: percentage decrease = total decrease in score / baseline score ×100. The hypothesis stated that a difference exists in efficacy between the two isotretinoin regimens. Methods: A total of 60 patients of both gender with Acne vulgaris were included in the study. Patients were divided in two groups, A and B. Each group had 30 patients. The initial assessment of acne was done by using GAGS score (global acne scoring system). In group A, patients were prescribed 20 mg oral isotretinoin once daily for 6 months and in Group B patients were prescribed intermittent regimen - 20 mg oral isotretinoin on alternate day for 6 months. Efficacy was noted by lesion counts from both groups, on monthly basis for 3 months and a follow up visit at 6 months. Results: Age range in this study was 18 to 40 years with mean age of 24.866±3.29 years and mean GAGS score was 28.266±2.79 in Group A and mean age of 25.266±3.67 years and mean GAGS score was 28.533±3.12 in Group B. Efficacy was observed in 27 (90%) patients in group A as compared to 25 (83.3%) patients in group B (p=0.447). Conclusion: In conclusion, the present study demonstrates that the low-dose continuous and low-dose intermittent oral isotretinoin regimens have comparable efficacy at the end of treatment.